World development report 1981. - World Bank; World Bank. (Washington, D.C. The World Bank, 1981)
This is the fourth in the World Bank's annual series assessing key development issues. Adjustment, global and national, to promote sustainable growth in the changing world economy is the main theme of this report. Recession and inflation in the industrial countries, together with the rise in oil prices, have been the main forces at work in the world economy in the 1970s. The report examines their effect on developing countries to see how adjustment has been managed and what lessons may be learned for the 1980s. Adjustment occurs through international trade and capital flows and through changes in national production and consumption patterns. The earlier chapters of the report present global and regional projections for the 1980s and consider international aspects of adjustment in trade, energy and finance. It then turns to adjustment problems of different groups of developing countries and a consideration of the prospects for human development. The report also includes the 1981 World Development Indicators, a set of 25 tables of economic and social indicators for 124 countries.
Keywords: Economic assistance; Underdeveloped areas -- Economic conditions; Underdeveloped areas -- Economic indicators